2015
DOI: 10.15386/cjmed-381
|View full text |Cite
|
Sign up to set email alerts
|

Infantile hemangioma: a brief review

Abstract: Infantile hemangiomas as frequent infancy tumors have been a controversial issue of medical scientists worldwide. Their clinical aspects are various and their physiopathology is yet to be fully understood. Numerous publications outline the characteristics, causes, evolution possibilities and therapeutic approaches. Deciding whether to treat or not is the main question of this kind of pathology. Hemangiomas that have complications or can cause irreversible damage need therapy. This is a brief review of up-to-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
0
13
0
2
Order By: Relevance
“…Although benign neglect is the cornerstone for its treatment, sometimes the final results are unpredictable and incomplete, moreover the time period for complete involution is not definite. This time period may cause severe parents anxiety; therefore, intervention is required [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Although benign neglect is the cornerstone for its treatment, sometimes the final results are unpredictable and incomplete, moreover the time period for complete involution is not definite. This time period may cause severe parents anxiety; therefore, intervention is required [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…7 Both previous studies and physical manifestations have indicated the presence of hypoxic condition and its promotive role in IH. 8,9 However, the precise mechanism accounting for hypoxia-mediated IH progression has not been fully clarified. Therefore, it is essential to discover novel molecular events underlying this process, which may provide better insights into the biological course of IH.…”
Section: Research-article2017mentioning
confidence: 99%
“…Infantile hemangiomas (IH) are the most common benign tumor in infants and occur in 5-10 % of children [1]. According to the classification of the International Association for the Study of Vascular Anomalies (ISSVA) 2018, hemangiomas are benign vascular tumors and include IH, as well as congenital hemangiomas (rapid-involving, partially involute, non-involute) [2].…”
Section: Problem Descriptionmentioning
confidence: 99%